1992
DOI: 10.4315/0362-028x-55.9.701
|View full text |Cite
|
Sign up to set email alerts
|

Hazards and Critical Control Points of Street-Vending Operations in a Mountain Resort Town in Pakistan

Abstract: Hazard analyses (which included watching operations, measuring temperatures of foods throughout preparation and display, and sampling and testing for microorganisms of concern) were conducted of vending operations of chicken, rice, pulse patties, and ice cream in a resort town in Pakistan. Salmonellae were isolated from ground meat, chicken flesh (from all operations surveyed), cutting boards, egg shells (eggs used in pulse patties), and buffalo milk (used for milk shakes). Greater than 105 coliform bacteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 14 publications
0
14
0
9
Order By: Relevance
“…Foods are often held for several hours after cooking and this includes overnight holding at ambient temperatures, until sold, and thus can harbor high microbial populations [7,10,11,38,39,56]. Besides, some of the foods are held in the pans in which they are cooked, until sold or reheated, which results in longer holding time, hence creating favorable conditions for the growth of foodborne pathogens.…”
Section: Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Foods are often held for several hours after cooking and this includes overnight holding at ambient temperatures, until sold, and thus can harbor high microbial populations [7,10,11,38,39,56]. Besides, some of the foods are held in the pans in which they are cooked, until sold or reheated, which results in longer holding time, hence creating favorable conditions for the growth of foodborne pathogens.…”
Section: Storagementioning
confidence: 99%
“…[8][9][10][11][12][13][14]. People who patronize street food, have been reported to suffer from food borne diseases like diarrhea, cholera, typhoid fever and food poisoning [15][16][17][18][19].…”
mentioning
confidence: 99%
“…Only the sample skewer cooked complies against all searched germs. Other studies (Bryan et al, 1992) reported that cooking and food exposure at room temperature are two important critical points at street food. Then cooked skewers are arranged on trays for sale.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Cross-contamination is a serious risk in food vending due to inadequate knowledge on how to control it which puts the consumers of such foods at high risk of buying contaminated ready-to-eat food [18]. It is normally hard to trace the source of contamination during incidences where cross-contamination occurs as a result of intermixing products and criss-crossing of food vendors [19].…”
Section: Conformity To Recommended Hygiene Conditions Of Food Preparamentioning
confidence: 99%
“…Food handling personnel play an important role in ensuring food safety throughout the chain of food preparation [19]. Food borne outbreaks are generally due to poor personal hygiene of food vendors [2].…”
Section: Conformity To Recommended Hygiene Conditions Of Facilities Fmentioning
confidence: 99%